2014
DOI: 10.1177/0748730414540453
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Role for the REV-ERBα–Controlled L-Type Voltage-Gated Calcium Channel CaV1.2 in Resetting the Circadian Clock in the Late Night

Abstract: Within the suprachiasmatic nucleus (SCN) of the hypothalamus, circadian timekeeping and resetting have been shown to be largely dependent on both membrane depolarization and intracellular second-messenger signaling. In both of these processes, voltage-gated calcium channels (VGCCs) mediate voltage-dependent calcium influx, which propagates neural impulses by stimulating vesicle fusion and instigates intracellular pathways resulting in clock gene expression. Through the cumulative actions of these processes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 35 publications
1
47
0
Order By: Relevance
“…We reported previously that the BD-associated differences in amplitude under lithium-treated conditions involved calcium [13] and ERK signaling [12], pathways involved in photic entrainment in the SCN [14, 15, 18, 19]. The relative decrease in amplitude in the BD samples under both lithium treatment and entrained conditions may imply a loss of function in one or more of these pathways in BD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported previously that the BD-associated differences in amplitude under lithium-treated conditions involved calcium [13] and ERK signaling [12], pathways involved in photic entrainment in the SCN [14, 15, 18, 19]. The relative decrease in amplitude in the BD samples under both lithium treatment and entrained conditions may imply a loss of function in one or more of these pathways in BD.…”
Section: Discussionmentioning
confidence: 99%
“…Phase advances occur through glutamate signals to the master clock in the suprachiasmatic nucleus (SCN) that activate voltage-dependent LTCC, and subsequent stimulation of protein kinase G [14]. Mutant mice with forebrain selective knockout of Cacna1c expression show normal circadian rhythms under constant dark conditions, but they show a reduced ability to phase advance after a light pulse in the late night [18]. Both phase delay and phase advance pathways converge on the ERK to induce PER1/2 expression [19].…”
Section: Introductionmentioning
confidence: 99%
“…Its loss affects the ability to phase advance wheel running behavior in mouse after a light pulse and impairs the induction of Per2 and Per1 expression (26). In multiple GWASs (genome-wide association studies), CACNA1C has shown genome-wide significant associations to BP (27)(28)(29) as well as to other psychiatric disorders (27).…”
Section: Discussionmentioning
confidence: 99%
“…Also, lithium may affect circadian rhythms through signaling pathways other than GSK-3β. For example, chronic treatment of astrocytes with lithium causes a pronounced inhibition of K + -mediated increase in intracellular Ca 2+ , which is known to affect circadian period and other rhythm properties [17, 21, 25]. Further investigations are necessary to fully understand the signaling pathways through which lithium affects circadian rhythms.…”
Section: Discussionmentioning
confidence: 99%